Impact of Shaggy Aorta in Patients with Abdominal Aortic Aneurysm Following Open or Endovascular Aneurysm Repair. Issue 5 (November 2016) - Kwon, H.; Han, Y.; Noh, M.; Gwon, J.G.; Cho, Y.-P.; Kwon, T.-W.
Abstract : Objective: To analyze the impact of the presence of shaggy aorta on 30 day morbidity and mortality and long-term survival in patients undergoing abdominal aortic aneurysm (AAA) repair. Methods: This retrospective observational study included 447 consecutive patients who underwent AAA repair between January 2009 and December 2012. The study included 209 patients (47%) having open surgical repair (OSR) and 238 patients (53%) having endovascular aneurysm repair (EVAR). Results: Of the 447 patients having elective AAA repair, 48 patients (11%) had shaggy aorta. Both the OSR ( p  = .005) and EVAR group ( p  = .007) demonstrated a higher 30 day morbidity and mortality in patients with shaggy aorta. On multivariate regression analysis, patients with shaggy aorta had 4.1 fold (95% CI = 1.7–9.7; p  = .002) increase in 30 day morbidity and mortality. According to the Kaplan-Meier analysis, patients with shaggy aorta had significantly decreased long-term overall survival in comparison with the non-shaggy group (log-rank test; p  = .005), and this resulted from comorbidities. Conclusions: Shaggy aorta is a prominent risk factor associated with 30 day morbidity and mortality. Poor long-term survival was expected in patients with shaggy aorta.